The effectiveness of a peer coaching intervention on co-teachers' use of high leverage practices. Issue 1 (3rd January 2023) - Ackerman, Kera B.; Whitney, Todd; Samudre, Mark D.
Abstract: Co-teaching is a prevalent model to address student needs in an inclusive classroom, therefore it is critical that both the general and special education teacher are implementing high leverage and evidence-based practices. The present study used peer coaching in an elementary co-taught classroom to evaluate the effectiveness of teachers' use of high leverage practices to engage and provide feedback to students. Results showed that peer coaching was effective in increasing the use of these practices during intervention, however maintenance did not approximate the performance in the intervention condition. Future implications regarding the impact of these practices on at-risk student engagement in collaborative settings are discussed.